Walking through England: The Phenomenon of “Travelog” in the English Graphics of the 17th-18th Centuries - Arutyunyan, Julia I. (Actual Problems of Theory and History of Art, 2018)
The theme of traveling in the English graphics of the 17th-18th centuries unites four basic motives: images of one’s native country, impressions of the Italian Grand Tour, a trip through Europe, and a visit to the East. In the images of England — its views, types, roads, places of interest, and manors, the expressive language of English art reaches its maximum strength. The series of prints, most often etchings, represent the most important images of native history and the culture of the region in the context of their infinity frame. Long before the formation of the tendencies of the English “Gothic revival”, the appeal to medieval constructions reflects the interest in the historical heritage of the country. The images of well-arranged mansion surrounded by a regular park and other buildings are the main theme of English panoramic landscape. The stylistic evolution of prints indicates the path followed from the late-baroque decorative understanding of space with its conventional illusion to narrative description of a journey, from the interest to a specific building or construction to the emotionally romantic perception of the landscape. In the interpretation of architecture in graphics, there are two different vectors — the direction of a scientific understanding of form and style, on the one hand, and the creative processing of experiences and the trends of artistic interpretation of a theme on the other.